2018
DOI: 10.3390/antiox7120193
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Newborn Period: Useful Biomarkers in the Clinical Setting

Abstract: Aerobic metabolism is highly efficient in providing energy for multicellular organisms. However, even under physiological conditions, an incomplete reduction of oxygen produces reactive oxygen species and, subsequently, oxidative stress. Some of these chemical species are highly reactive free radicals capable of causing functional and structural damage to cell components (protein, lipids, or nucleotides). Oxygen is the most used drug in ill-adapted patients during the newborn period. The use of oxygen may caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…The results of these determinations are expressed as ratios, such as the o-Tyr/Phe, m-Tyr/Phe, 3NO2-Tyr/p-Tyr, and 3Cl-Tyr/p-Tyr ratios. These markers have been validated and extensively applied in the clinical setting in various human biofluid matrices, such as amniotic fluid, urine, plasma, cerebrospinal fluid, or human milk in the newborn period [16,24,29,31,36,[61][62][63][64]. In urine, in a pre-clinical study conducted on pig pups, we found a significant increase in both urinary o-tyrosine and 8-oxodG levels after 15 min of hyperoxia by resuscitation [62].…”
Section: Proteinsmentioning
confidence: 74%
See 4 more Smart Citations
“…The results of these determinations are expressed as ratios, such as the o-Tyr/Phe, m-Tyr/Phe, 3NO2-Tyr/p-Tyr, and 3Cl-Tyr/p-Tyr ratios. These markers have been validated and extensively applied in the clinical setting in various human biofluid matrices, such as amniotic fluid, urine, plasma, cerebrospinal fluid, or human milk in the newborn period [16,24,29,31,36,[61][62][63][64]. In urine, in a pre-clinical study conducted on pig pups, we found a significant increase in both urinary o-tyrosine and 8-oxodG levels after 15 min of hyperoxia by resuscitation [62].…”
Section: Proteinsmentioning
confidence: 74%
“…These are non-enzymatic products from the oxidation of amino acid-free radicals and other PUFAs, and are chemically stable. These compounds have been detected electively in lipid-rich tissues, such as brain tissue, which, being rich in polyunsaturated lipids, is highly sensitive to oxidative stress [ 16 , 17 , 18 , 19 , 20 , 21 , 25 , 29 , 30 , 33 , 34 , 35 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 61 , 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations